2022
DOI: 10.3390/nano12152656
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fine Particulate Matter 2.5 on the Cardiovascular System: A Review of the Invisible Killer

Abstract: Air pollution exerts several deleterious effects on the cardiovascular system, with cardiovascular disease (CVD) accounting for 80% of all premature deaths caused by air pollution. Short-term exposure to particulate matter 2.5 (PM2.5) leads to acute CVD-associated deaths and nonfatal events, whereas long-term exposure increases CVD-associated risk of death and reduces longevity. Here, we summarize published data illustrating how PM2.5 may impact the cardiovascular system to provide information on the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 206 publications
2
15
0
Order By: Relevance
“…These findings are consistent with previous literature, which has established that PM 2.5 is a risk factor for CVDM. [28,29] Previous literature also supports our findings of a seasonal effect of PM 2.5 on CVDM, but is split on whether cold or warm season exposure presents greater risk. [3033] Others have suggested that humidity, not temperature, is the primary driver of observed seasonal differences in CVDM associated with PM 2.5 concentrations.…”
Section: Discussionsupporting
confidence: 88%
“…These findings are consistent with previous literature, which has established that PM 2.5 is a risk factor for CVDM. [28,29] Previous literature also supports our findings of a seasonal effect of PM 2.5 on CVDM, but is split on whether cold or warm season exposure presents greater risk. [3033] Others have suggested that humidity, not temperature, is the primary driver of observed seasonal differences in CVDM associated with PM 2.5 concentrations.…”
Section: Discussionsupporting
confidence: 88%
“…The toxicity of fine and nanoscale particles is highly dependent on the composition of the particles due to physicochemical differences of the materials and differences in toxicity of the composed chemicals ( 22 , 42 ). Moreover, the composition of the PM 2.5 varies according to PM 2.5 sources, including region, natural circumstance, and anthropogenic factors ( 43 ). In this study, we evaluated the toxicity of diesel-derived PM 2.5 , which is certified as Standard Reference Material (SRM) by the National Institute of Standards & Technology (NIST), and the PM 2.5 is composed with polycyclic aromatic hydrocarbons (PAHs) and nitro-substituted polycyclic aromatic hydrocarbons (Nitro-PAHs) ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is less attention to the effect of dust storms on workers with a specific physical activity. Most of them were focused on human health effects due to industrial particles 18 , 24 . Besides, there are no published studies to investigate the effects of HMs associated with airborne particles on the CB based on our best knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they penetrate the blood Circulatory system and then can damage other tissues 16,17 . The American Heart Association has argued that heart disease and mortality associated with PM may relate result of systemic inflammation and endothelial dysfunction 18,19 . Some studies have shown that exposure to PM 10 has been significantly associated with cardiovascular and respiratory diseases in residents near open-pit mining regions 15,[20][21][22] .…”
mentioning
confidence: 99%